PENGARUH BRAND TRUST, & KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR MATIC HONDA PADA PENGEMUDI GOJEK DI SURABAYA, JAWA TIMUR - Isnawati, Linda; Rafida, Veni (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2024)
The research was conducted to analyze the influence of Brand Trust, and product quality on the purchase decision of the matic motorcycle product of Honda on the Drivers in Surabaya. Respondents to this study were Online Driver or Driver in the city of Surabaya. In sampling, this study uses purposive samplings as its method. And the method of analyzing data using double linear regression and to analyze the data using SPSS 26. Based on the results of the data analysis, it was found that: 1) Brand Trust has a negative relationship to the decision of purchase of a motorcycle matic honda on Surabaya Online Driver. 2) product quality has an influence upon the decision to buy a motorbike matic Honda Online Driver Surabaya. 3) Brand Trust, and the quality of the product simultaneously influence the decision about the purchase of the motorcycling matic honda on Surabaya internet Driver.